Business Plan for Ade Farm Food Production Company NIG LTD - Aremu, Adejare Yusuff; Shola, Adediran Daud (International Research Journal of Management, IT & Social Sciences, 2016)
Ade Farmers Food Production is a family farms business, it focus to be produce more food in quantity and to be packaging in a different kg, also to be added to value of Nigeria economies and to be contribute  many benefit for communities. In addition, we have   plan to extend to many countries in Asia, like Malaysia, china, Dubai. Farmers Food production is the one of successful food farms. The idea behind the business is to provide healthy and delicious semovita and mails to the public. In addition to semovita and mails the company plans to produce and market manure compost garden amendment products. Farmers Food productions being formed from the  family  successful food farms, The latter has long-researched horticultural and agronomic techniques, as well as compost and land blending technology now being promoted by the farmer association of Oyo state  agencies. The company is a combination of cutting edge, highest quality, and efficient food technology and production. It is committed to the improvement of food production in the nation and nutritional quality. It is being founded to build upon an extensive array of biological and horticultural education, experience, and the research of its founders. This is further coupled with the experience of Mr. Akeeb, the current manager of  Farmers Food Farm, and consultation with the present owner of Food Farm, Mr. Ademola A.A. Farmers Food production is a Kisi-based company, located in Oyo state Nigeria, whose mission is to provide high quality, nutritional, and flavorful semovita and gari for consumption in both near and remote regions of the Nigeria. Additionally the company will provide high quality planting materials for use nationwide.